AN OVERVIEW OF THE LEVEL OF KNOWLEDGE ON SELF-MEDICATING VITAMIN C STUDENTS D III PHARMACY STIKES WDH TANGERANG DURING THE COVID-19 PANDEMIC - Anis Dwi Kristiyowati (SEKOLAH TINGGI ILMU KESEHATAN NASIONAL, 2023)
Background: Vitamin C is an essential water-soluble vitamin that is widely used as a body supplement. Misuse of the dosage will cause unwanted side effects such as nausea vomiting, diarrhea, increasing the risk of diabetes. Purpose: This study is to find out an overview of the level of knowledge on self-medicating the use of vitamin C for D III Pharmacy students of STIKes Widya Dharma Husada Tangerang during the Covid-19 pandemic. Method: This study is a descriptive study with 96 respondents taken by the cross-sectional method. Data were obtained through questionnaires and analyzed using percentages. Results: The results obtained in this study are the characteristics of respondents based on age Most of them are found at the age of 17-25 years, namely 87.5%, based on gender Most of them are found in women, namely 84.37%, based on work more than half of them are found in those who are not working, namely 52.08%, and based on a history of exposure to covid-19 more than half of them are found in those who have been exposed to covid-19, namely 73.96%, while the characteristics of respondents' knowledge about the use of well-informed vitamin C were highest based on the age of 17-25 years as much as 84.37%, in the female sex as much as 81.25%, in unemployed work as much as 50%, in the history of exposure to covid-19 who had been exposed to covid-19 as much as 70.83%. Conclusion: The results of this study show that the concentration of the level of knowledge on self-medicating the use of vitamin C for D III Pharmacy students of STIKes Widya Dharma Husada Tangerang during the Covid-19 pandemic was 96.88% included in the